Is technology-enhanced feedback encouraging for all in Finnish basic education? A person-centered approach. (December 2018) - Oinas, Sanna; Vainikainen, Mari-Pauliina; Hotulainen, Risto
Abstract: In Finnish basic education, the majority of teachers give technology-enhanced feedback about learning and behaviour on a daily basis by clicking predefined options in an online platform. In this study, we explored 211003 feedback actions given by 704 teachers to 7811 pupils and their parents using latent profile analysis. Information on individual support needs was used to evaluate whether all pupils are equally encouraged by technology-enhanced feedback. We identified six subgroups for girls and five for boys. Highly encouraging feedback was given mostly to pupils who were rarely absent and who more seldom had special education needs. Negative feedback about behaviour problems was given mostly to boys and the majority of pupils were encouraged only weakly. On average, pupils received feedback according to three different profiles in a single teaching group. We concluded that technology-enhanced feedback in its current form is not equally encouraging for all. Highlights: Technology-enhanced feedback is not equally encouraging for all. 211 003 feedback notes for 7811 pupils were analysed using latent profile analysis. Pupils were identified to be encouraged Highly, Averagely or Weakly. Pupils with special education needs were more likely to be only Averagely or Weakly encouraged. Negative feedback about behaviour problems was given mostly to boys.